Collagenase Management of Multicord Dupuytren's Disease under Intravenous Sedation: A Prospective Cohort Study. Issue 2 (February 2019) - Wiseman, Jeremy; Tree, Kevin; Guio-Aguilar, Pedro; Pratt, George; Nizzaro, Danielle; Leung, Michael; Leong, James
Abstract : Background: Surgery has been the standard of care in managing Dupuytren's disease (DD). Recently collagenase of Clostridium histolyticum (CCH) has provided a less invasive alternative. The purpose of the current study is to present the early outcomes of a protocol for CCH involving treatment of multi-cord disease, and large patient cohorts. Methods: A cohort of 137 consecutive patients (Mean age 66 years, SD 9.85) with 225 joint contractures was treated with CCH at our institution between December of 2014 and January of 2017. A single standardized concentration of collagenase 2.31 mg/ml or 0.58 mg/dose was used for the treatment of up to 5 cords at a single session, and manipulation was 48 hours post-injection under intravenous sedation (IV). Patient complications, reduction in joint contracture, patient satisfaction and patient reported functional outcomes were assessed after one month. Results: 137 patients received a total of 214 doses 0.58mg of CCH to treat 225 PIP and MCP joint contractures. The mean correction of joint contractures was 39.8 ± 2.2 and 27.9 ± 3.9 degrees for MCP and PIP joints respectively. 80% of patients, reported improved function and 89% of patients who were satisfied with the treatment. Conclusions: This study demonstrates a protocol for high throughput management of DD using collagenase and IV sedation for manipulation, logistically suited to the hospital setting. Efficacy was demonstrated treating patients with up to 5 cords, including those with bilateral disease. Future studies are needed to evaluate the durability of response in the medium and long term, and to evaluate cost benefits.